BEHAVIOR OF RC BUILDING WITH AND WITHOUT INFILL WALL UNDER BLAST LOADING - Saidou, Sabiou Namata; Kocak, Ali (YILDIZ TECHNICAL UNIV, 2018)
In this work the authors intended to improve the knowledge regarding to RC and masonry structures subjected to blast loading. A further aim is to describe and use the non-linear-finite element method through a comparison of RC building with and without infill wall. In order to perform the models subjected to analysis, based on existing experimental studies of infill wall and RC columns, by using the FE method, the blast loading is simulated using conventional weapons for explosion model where it was generated with 1000kg of TNT explosive material at a distance of 4.6m. For the finite element model of the building, bricks and mortar joints are represented by continuously cohesive elements and contact elements were used to simulate the adhesion and interaction between the blocks. The nonlinear behavior of the concrete and masonry were simulated using the Coupled Damage Plasticity methods. Simulation results showed that compressive and tensile strengths increase due to the strain rate effect and the initial stiffness increases.
Keywords: Building; infill wall; blast; masonry; finite element; Engineering